Freshwater pond fish farming in Bangladesh: A micro level land use analysis - Palash, Md Salauddin; Rahman, Kazi Tamim; Salam, Shakila; Nasrin, Mahmuda (Journal of the Bangladesh Agricultural University, 2018)
Market-oriented farming has been started in Bangladesh over last two decades. As a consequence, diversified agricultural products are now produced which changing the land use pattern. This study conducted in Trishal upazila of Mymensingh district, a major freshwater pond fish farming area of Bangladesh. Secondary data from different relevant government offices (Upazila Agriculture, Fisheries, and Statistical office) were collected to find out how much cropland has been converted to pond fish farming and what will be the future trend of land use in the afore mentioned area. Total land area of Trishal sub-district is 33876 ha and since last three-decade cropland has been converted to commercial freshwater fish farming. As a consequence, the area under commercial fish farming is now 4542 ha (13.41 per cent total area of Trishal upazila); which was only 1920 ha in the year of 2010. The commercial fish farming land area was converted mostly from cropland area and then a little portion came from Khas (Government owned fallow land) and fallow land area. Within six years (2010-2016), agricultural cropland area had decreased by 6.68 percent (1.11 per cent per year) and pond fish farming area had increased by 7.74 percent (1.29 percent per year). By 2021, following non-linear (quadratic) trend projection model, about 2000 ha more land will be occupied by pond fish farming. J. Bangladesh Agril. Univ. 16(2): 276-282, August 2018